Soil ecotoxicity of seven endocrine‐disrupting chemicals: a review. (7th September 2017) - Kwak, J. I.; Moon, J.; Kim, D.; An, Y.‐J.
Abstract : Endocrine‐disrupting chemicals (EDCs) are widely used in manufacturing, and they enter the soil by direct and indirect pathways. Thus, there are concerns about their potential effects on soil ecosystems and some studies have monitored EDCs in the soil environment. However, there have been few studies on soil ecotoxicity of EDCs so far compared with aquatic ecotoxicity, and there is no comprehensive review of soil ecotoxicity of EDCs. Therefore, we collected, compiled and reviewed 77 studies on the soil ecotoxicity of seven prominent EDCs: bisphenol A, di(2‐ethylhexyl) phthalate (DEHP), nonylphenols, triclosan, polybrominated diphenyl ethers (PBDEs), perfluorooctanoic acid (PFOA) and perfluorooctane sulphonate (PFOS). This review brings together the data on soil ecotoxicity and research trends for these seven EDCs and identifies the need for further research to fill the gaps in our knowledge and data. Highlights: Endocrine‐disrupting chemicals (EDCs) pose potential threats to soil ecosystems. Seventy‐seven studies on the soil ecotoxicity of seven EDCs were reviewed. There are fewer studies on soil ecotoxicity than on aquatic ecotoxicity. Further research including various environmentally relevant concentrations of EDCs is needed.